Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0974-777x.112288
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors of helicobacter pylori infection and peptic ulcer disease

Abstract: Background:Helicobacter pylori (H. pylori) infection is a risk factor for peptic ulcer. There have been no studies addressing environmental and dietary risk factors in western India. We conducted a case control study enrolling peptic ulcer patients in Pune, India.Materials and Methods:Risk factors for peptic ulcer and H. pylori infection were assessed in a participant interview. H. pylori status was assessed from stool by monoclonal antigen detection.Results:We enrolled 190 peptic ulcer, 35 stomach cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 33 publications
(33 reference statements)
5
42
1
2
Order By: Relevance
“…Mhaskar et al [16] reported the high prevalence of peptic ulcer and H. pylori infection in patients associated with meat and meat products and restaurant foods which confirm the results of our study. High amount of Aw in meat base food samples, optimum pH and salt levels, presence of appropriate levels of amino acids including arginine, histidine, isoleucine, leucine, methionine, phenylalanine, alanine, valine, proline, serine, and tryptophan favors the for growth of H. pylori [12], this is in addition to unsanitary conditions in their preparation and cross contamination of these foods due to handling by factory and food units staffs.…”
Section: Discussionsupporting
confidence: 82%
“…Mhaskar et al [16] reported the high prevalence of peptic ulcer and H. pylori infection in patients associated with meat and meat products and restaurant foods which confirm the results of our study. High amount of Aw in meat base food samples, optimum pH and salt levels, presence of appropriate levels of amino acids including arginine, histidine, isoleucine, leucine, methionine, phenylalanine, alanine, valine, proline, serine, and tryptophan favors the for growth of H. pylori [12], this is in addition to unsanitary conditions in their preparation and cross contamination of these foods due to handling by factory and food units staffs.…”
Section: Discussionsupporting
confidence: 82%
“…Helicobacter pylori infect about 50% of the world's population . And many cases of peptic ulcers, gastritis, and duodenitis are confirmed to have an association with H. pylori infection . In addition, infection with cytotoxin‐associated gene A (CagA)‐positive strains of H. pylori increases the risk associated with H. pylori infection alone .…”
Section: Introductionmentioning
confidence: 99%
“…The Karen Hill population uses extreme levels of chili, grown and produced in their villages. However, chili has been claimed to be protective against H. pylori infection as well as peptic ulcer [33]. The influence of diet on stomach pain and specifically on gastritis and peptic ulcer is still unclear and needs to be studied separately [2].…”
Section: Discussionmentioning
confidence: 99%